Enhanced red blood cell distribution width to platelet ratio is a predictor of mortality in patients with sepsis: a propensity score matching analysis based on the MIMIC-IV database. Issue 9 (23rd September 2022) - Zhou, Yuanjun; Zhong, Liping; Chen, Weiming; Liang, Fei; Liao, Yilin; Zhong, Yuting
Abstract : Objective: To explore the association between dynamic changes in red blood cell distribution width to platelet count ratio (RPR) during hospitalisation and short-term mortality in patients with sepsis. Design: A retrospective cohort study using propensity score matching. Setting: Intensive care units (ICUs) of Beth Israel Deaconess Medical Center. Participants: A total of 8731 adult patients with sepsis were included in the study. The patients were identified from the ICU of the Medical Information Mart for Intensive Care database. The observed group included patients who experienced an increase in RPR of more than 30% during the first week of ICU admission, whereas the control group included the rest. Main outcome and measure: Using propensity score matching, a matched control group was created. The primary outcome was 28-day mortality, and the length of hospital stay and in-hospital mortality were the secondary outcomes. Results: The difference was evident in 28-day mortality between the two groups (85.8% vs 74.5%, p<0.001, Kaplan-Meier analysis, and HR=1.896, 95% CI=1.659 to 2.168, p<0.001, Cox regression). In the secondary outcomes, there was a significant difference in in-hospital mortality (p<0.001). In addition, the study discovered that the observed groups had a significantly longer hospital stay (p<0.001). Meanwhile, the results of subgroup analyses were consistent with those of the primary analyses. Conclusions: In patients with sepsis, a significantly increased RPR is positively associated with the short-term death rate. Continuous RPR monitoring could be a valuable measure for predicting short-term mortality in patients with sepsis.